Connectivity, landscape structure, and plant diversity across agricultural landscapes: novel insight into effective ecological network planning. (1st September 2022) - Liccari, Francesco; Boscutti, Francesco; Bacaro, Giovanni; Sigura, Maurizia
Abstract: Natural habitats in rural and urban areas are increasingly fragmented and altered by human impacts that are limiting the animal and plant dispersal process. Fragmentation and isolation can be reversed by restoring landscape connectivity through effective Ecological Network (EN) planning. However, most of the studies analyzing the influence of connectivity and landscape structure on biodiversity are focused on animals, while the understanding of their interplaying role on plant diversity remains limited. We studied the relationships between α and β diversity pattern and landscape structure and connectivity in the nodes of an EN developed in agricultural landscapes, as a part of regional landscape planning framework in Friuli Venezia Giulia region (North-East of Italy). As an innovation, the study aims at parsing the interacting effect of landscape structure, surrounding habitats and nodes, and structural connectivity on EN plant diversity at two specific scales of investigation i.e., the habitat and the node scale. The habitat was the basic ecological unit, while the node was the basic cartographical unit for the EN mapping (multi-habitat or mono-habitat nodes). A total of 443 plant species were collected across 219 sample plots, in 14 different habitats and 87 nodes of the EN. We found that high node connectivity leads to higher species richness (α-diversity) but also increases plant community similarity (i.e., low β-diversity) at both scales. The effect of landscape structure showed differing trends depending on the habitat. In general, landscape composition of semi-natural land cover (i.e., hedgerows, watercourses) showed a positive effect on species diversity as opposed to that of the configuration of anthropogenic elements on both scales. Our results provided crucial information on the landscape processes useful to improving biodiversity conservation by EN. Our findings suggest that i) improving connectivity within ENs favors α plant diversity ii) different habitats have different sensibility to landscape structure iii) semi-natural land cover around nodes improve plant diversity; iv) planning both mono-habitat and multi-habitats nodes, increases the biodiversity conserved therein; v) nodes with more compact shapes are to be preferred. Highlights: The understanding of the influence of connectivity and landscape structure on plant diversity is limited. Both α and β diversity were considered as response variables. The effects of connectivity and landscape structure on plant diversity were investigated at two scales. Improved connectivity leads to greater species richness but also increases community similarity. Our results provided crucial information useful to improving biodiversity conservation by EN.